(untitled) (International journal of artificial intelligence, 2025)
Language and culture are inseparable phenomena. Linguoculturology studies how linguistic units reflect the worldview, mentality, and traditions of a particular nation. In literature, this interconnection manifests through artistic and linguistic devices that carry cultural meanings. Both Abdulla Qodiriy, a pioneer of modern Uzbek prose, and Jack London, a representative of American naturalism, vividly express the cultural and social essence of their nations through their language and style.